Why do rural youth migrate? Evidence from Colombia and Guatemala - Díaz Baca, Manuel Francisco; Moreno Lerma, Leonardo; Burkart, Stefan; Triana Ángel, Natalia (Frontiers in Sociology, 2024)
Migration, from rural to urban settings is a common phenomenon in Latin America, due to social, economic, political, and other factors. Young people in search of economic and educational opportunities, financial, and social stability, have been migrating to larger urban centers, thus crafting important shifts in rural labor, generational transfer, and domestic economies. Through a systematic literature review of scientific literature, and documents from public institutions and international organizations, published between 2012 and 2022, this article addresses rural–urban migration of youth in Colombia and Guatemala’s cattle sector, particularly identifying (i) driving factors, (ii) their impacts on cattle farming, and (iii) public policies implemented to counteract prejudicial effects. Results show that unemployment, lack of educational opportunities, and insecurity are the main reasons for youth migration to cities or abroad, with Mexico, the United States, and Spain being the most common destinations. Additionally, impacts on the cattle sector include shortage of labor and a perfectible generational transfer, hindering the modernization of the industry and investments in climate change adaptation and mitigation strategies. Despite various implemented public policies, the results are partial, and the issue of accelerated youth migration remains relevant. Consequently, without more effective measures adopted by national governments, the cattle sector will lag behind its regional and international competitors, deterring the achievement of the Sustainable Development Goals. As the main contribution of the study, the analysis of migration is highlighted based on its effects on a specific economic sector and not focused on its causes, as evidenced in a wide range of literature.